(untitled) (Literasi Nusantara, 2022)
In classroom teaching, the role of the teacher greatly influences the application of the appropriate learning model that engages students’ thinking actively. Lecture methods are often used by teachers when instructing students. Therefore, it is necessary to utilize the right methods for effective learning, especially in improving narrative text writing. One proposed solution is to implement a teaching model that can enhance students’ narrative text writing. The teaching model in question is Problem Based Learning (PBL). This article discusses the application of the PBL model in teaching narrative text writing. This research aims to explore how the PBL model is applied in teaching narrative text writing in Grade V at SD Negeri 101953 Pantai Cermin. The research methodology employed in this study is qualitative research using a descriptive qualitative research method. Data were collected through research instruments such as observation, interviews, and documentation. Data analysis involved data reduction, data presentation, and drawing conclusions. The results of this study indicate that the application of the PBL model has a significant impact on the success of the narrative text writing learning process. This can be observed through the shift from the traditional lecture method used by teachers in teaching narrative text writing to the more effective Problem Based Learning model. This shift has resulted in a more active and enjoyable classroom environment, with students transitioning from passivity to actively engaging in problem-solving. Therefore, the application of the Problem Based Learning model is highly effective in enhancing students’ creativity and the overall quality of learning.